No net land take policy in practice: Applications and potentials of planning instruments in municipalities. Results of an online survey in North Rhine-Westphalia - Sebastian Eichhorn; Brigitte Adam; Kerstin Schürholt; Stefan Baumann; Silas Eichfuss; Hendrik Jansen; Theo Kötter; Natascha Rohde; Jan Matthias Stielike; Thomas Terfrüchte; Johannes Wilberz (Raumforschung und Raumordnung, 2023)
In line with the European Commission’s target, land take in Germany has to be reduced to net zero by 2050. This not only presupposes greater inner urban development and more efficient development outside existing settlements, but also puts a greater planning and political focus on renaturation. The aim of this paper is to investigate the implementation of no net land take policy using the example of the highly dense and urbanised federal state of North Rhine-Westphalia in Germany. Based on an online survey, the current and potential use of (planning) instruments to implement this policy in all 396 municipalities in North Rhine-Westphalia was investigated. The findings suggest that the municipalities are not yet in a position to consistently implement no net land take. Particularly in the field of renaturation, this is often due to a lack of experience and uncertainties in the use of the existing (planning) instruments, but also to lacking awareness of the problem and a lack of political and social acceptance for higher housing densities. Since the necessary instruments are defined in current legislation and the concepts for implementation are generally known, it is important to support municipalities in using the available instruments and concepts even without direct pressure to act.